2009
DOI: 10.1371/journal.pone.0005897
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Dopamine in Drosophila Larval Classical Olfactory Conditioning

Abstract: Learning and memory is not an attribute of higher animals. Even Drosophila larvae are able to form and recall an association of a given odor with an aversive or appetitive gustatory reinforcer. As the Drosophila larva has turned into a particularly simple model for studying odor processing, a detailed neuronal and functional map of the olfactory pathway is available up to the third order neurons in the mushroom bodies. At this point, a convergence of olfactory processing and gustatory reinforcement is suggeste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
235
4

Year Published

2010
2010
2016
2016

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 175 publications
(249 citation statements)
references
References 110 publications
(187 reference statements)
10
235
4
Order By: Relevance
“…Flies were cultured according to standard methods. See the Supplemental Data (available at www.jneurosci.org as supplemental material) or Selcho et al (2009) for fly stock source. For the behavioral experiments, UAS-shi ts1 was crossed to the MB-specific GAL4-driver lines.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Flies were cultured according to standard methods. See the Supplemental Data (available at www.jneurosci.org as supplemental material) or Selcho et al (2009) for fly stock source. For the behavioral experiments, UAS-shi ts1 was crossed to the MB-specific GAL4-driver lines.…”
Section: Methodsmentioning
confidence: 99%
“…Interestingly, how other sensory modalities are signaled onto the MBs and how output neurons collect the information from the MBs is hardly understood. Recent findings suggest that dopaminergic and octopaminergic neurons signal aversive and/or appetitive reinforcement onto the MBs (Schwaerzel et al, 2003;Schroll et al, 2006;Claridge-Chang et al, 2009;Honjo and Furukubo-Tokunaga, 2009;Mao and Davis, 2009;Selcho et al, 2009). Anatomically Tanaka et al (2008) identified at least 24 different types of MB extrinsic neurons (MBENs) in adult flies.…”
Section: Introductionmentioning
confidence: 99%
“…2 A, B). Notably, unless mentioned otherwise, we here used only one odorant, n-amyl acetate (AM, CAS: 628 -63-7, purity: 99%, Merck) to simplify the paradigm (Selcho et al, 2009;Saumweber et al, 2011). That is, we train groups of 30 larvae each and compare olfactory choice performance after either of two reciprocal training regimens: one group was exposed to the odorant AM in the presence of a positive reinforcer and to a no-odor situation without the reinforcer (AMϩ/noAM); the second group was trained reciprocally, i.e., by unpaired presentations of odorant and reinforcer (AM/noAMϩ).…”
Section: Methodsmentioning
confidence: 99%
“…For example, you can measure the behavior toward AM of larvae that have received paired presentations of AM with the reward during one kind of trial and exposure to an unrewarded Petri dish with an odorless container during the other type of trial (AM+/empty); these larvae then must be compared with larvae that have received unpaired presentations of AM and reward (AM/empty+). Clearly, the test involves an AMfilled container on the one side and an empty container on the other (Selcho et al 2009).…”
Section: Experimental Designmentioning
confidence: 99%